2015
DOI: 10.1021/acs.jpcc.5b01647
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Design of Highly Stable Small Colloidal SERS Substrates with Supramolecular Host–Guest Interactions for Ultrasensitive Detection

Abstract: In this work, we report a simple strategy to obtain ultrasensitive SERS nanostructures by self-assembly of Au nanospheres (NSs). This novel protocol allow us to obtain in a reproducible manner Au NS dimers using cucurbit[6]uril (CB[6]) molecules as linkers. The resulting dimers are stable in colloidal dispersion over several days, generating in this way nanostructures with highly reproducible hot spots. This feature is due to the precise subnanometric control of the molecules that generates interparticle dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…This low density of metal nanostructures in the colloidal solution results in low sensitivity of SERS measurements, with the observed sensitivity usually 1 or 2 orders of magnitude lower than that observed for other substrate types. 18,19…”
Section: Introductionmentioning
confidence: 99%
“…This low density of metal nanostructures in the colloidal solution results in low sensitivity of SERS measurements, with the observed sensitivity usually 1 or 2 orders of magnitude lower than that observed for other substrate types. 18,19…”
Section: Introductionmentioning
confidence: 99%
“…italicAEF=ISERScnormalInormalcSERSIn contrast to SSEF, AEF is particularly useful for colloidal SERS substrates. 15 For solid substrates, large variations in AEF are expected due to variations in the way analyte molecules are added to the substrates, as such variations affect analyte adsorption to the substrate surface. Analyte adsorption to a SERS substrate is generally described using the Langmuir isotherm, 16, 17 such that the coverage of the analyte on the metal surface is only linearly correlated with the analyte solution concentration over a low concentration range.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a recent study, Fraire et al reported two AEF values that varied over five orders of magnitudes (1×10 8 vs. 3×10 3 ) corresponding to two different c SERS (i.e., 10 −11 vs. 10 −7 M). 15 Accordingly, AEF reflects the combined properties of both the SERS substrate and the number of analyte molecules on the surface rather than the intrinsic enhancing capability of the SERS substrate. As Le Ru stated, “It is not a good characterization of the SERS substrate itself, and it cannot be used to easily compare the performances of different substrates.”…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [ 36 ] Copyright 2015, American Chemical Society. c) 1D assembly of negatively charged NPs with CB[ n ]s and salts through electrostatic interactions.…”
Section: Applications Of Cb[n]s‐mediated Nmnpsmentioning
confidence: 99%